Bystander Attitudes to Hearing Family Violence: An Australian Survey - McInnes, Elspeth (International Journal of Criminology and Sociology, 2022)
Male violence against women and children is a pernicious global problem responsible for a high burden of injury, illness, and premature death across societies and cultures. Socio-cultural beliefs, attitudes, and practices underpin the conduct of perpetrators, targets, bystanders, and responding service providers, including police, health, and social welfare services. Bystanders’ willingness to act to help targets of family violence is a key dimension framing the social environment of using violence against family members. An anonymous internet survey of 464 Australians, mainly women, identified that around three-quarters of respondents would respond if they heard a cry for help from a nearby home. Most said they would call the police. The key deterrents to taking action were fears for their safety and their confidence that calling the police would lead to effective action. Despite their willingness to act, most believed that the typical Australian public would not do so. They attributed reluctance to take action to bystanders’ fears for their safety, beliefs that it was not their business, and not wanting to get involved. Respondents wanted more financial, housing, and legal support for victims of violence to end abusive relationships. Nationally consistent FDV laws, changes to media reporting, and school-based education were nominated as key strategies to prevent and reduce family and domestic violence.